2006
DOI: 10.1029/2005ja011470
|View full text |Cite
|
Sign up to set email alerts
|

Measuring noise in magnetometers: An example using the Mars Global Surveyor magnetometers

Abstract: [1] A recently developed data analysis tool allows direct measurement of the total root-mean-square noise in magnetometer data. Since the total is a combination of intrinsic instrument noise and solar wind magnetic field fluctuations, we can put upper limits on the instrument noise during periods of relatively quiet solar wind fields. The technique involves taking vector and scalar products of successive magnetic measurements; the resulting scalar quantity is insensitive to slow field variations as well as sud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The MV method just requires a well ordered large scale variance of B in the three spatial directions. MV has been extensively used to find the orientation of structures in the interplanetary medium (see e.g., Sonnerup & Cahill 1967;Burlaga & Behannon 1982;Hausman et al 2004;Siu-Tapia et al 2015). Several authors have shown that the MV method estimates quite well the orientation of the FR axis, when the distance between the axis and the spacecraft trajectory in the MC is small with respect to the FR radius (see e.g., Klein & Burlaga 1982;Bothmer & Schwenn 1998;Farrugia et al 1999;Xiao et al 2004;Gulisano et al 2005Gulisano et al , 2007Ruffenach et al 2012Ruffenach et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The MV method just requires a well ordered large scale variance of B in the three spatial directions. MV has been extensively used to find the orientation of structures in the interplanetary medium (see e.g., Sonnerup & Cahill 1967;Burlaga & Behannon 1982;Hausman et al 2004;Siu-Tapia et al 2015). Several authors have shown that the MV method estimates quite well the orientation of the FR axis, when the distance between the axis and the spacecraft trajectory in the MC is small with respect to the FR radius (see e.g., Klein & Burlaga 1982;Bothmer & Schwenn 1998;Farrugia et al 1999;Xiao et al 2004;Gulisano et al 2005Gulisano et al , 2007Ruffenach et al 2012Ruffenach et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…These eigenvalues are obtained by the diagonalization of the covariance matrix of the magnetic field. Nevertheless, several authors (Behannon et al 1981;Sckopke et al 2000;Khrabrov & Sonnerup 1998;Blanco et al 2003;Hausman et al 2004) have pointed out some problems when MVA is applied to magnetic discontinuities. One of these problems is related to the statistical nature of MVA and how to avoid degenerate eigenvalues, especially between medium and minimum ones.…”
Section: Introductionmentioning
confidence: 99%